HEALTH-RELATED QUALITY OF LIFE IN THE PATIENTS WITH THE SENSORINEURAL HEARING LOSS OF PROFESSIONAL GENESIS - Марина Пинхасовна Дьякович; Виктор Андреевич Семенихин; Светлана Наильевна Раудина (Медицина в Кузбассе, 2017)
Subject. Patients with sensorineural hearing loss (SNHL) of professional genesis.